ANALISIS KEPUASAN PETANI SAYURAN ORGANIK ANGGOTA GAPOKTAN BANGKIT MERBABU DALAM MENGIKUTI PROGRAM KEMITRAAN USAHA DENGAN PT BLOOM AGRO - Arsela, Yola; Roessali, Wiludjeng; Setiawan, Bambang Mulyatno (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
A partnership is an effort to involve various components to work together toward a common goal. This study aims to analyze the implementation of the partnership between farmers and PT Bloom Agro and to analyze the level of farmers’ satisfaction with the company. This study was conducted in January-February 2020 at the Bangkit Merbabu Farmer Group Association, Getasan Subdistrict, Semarang Regency. This study used a case study method with a sample size of 50 respondents who were determined by purposive sampling. Furthermore, the data were analyzed using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The study found ten attributes that are used as an assessment in implementing a partnership between farmers and PT Bloom Agro. The calculation from the Importance Performance Analysis (IPA) found one attribute that became the main priority (Quadrant I), namely the field technicians’ level of knowledge. The four attributes that need to be maintained (Quadrant II) are clear standard operating procedures regarding product quality determination, selling price suitability, ease of product delivery, and increased revenue. The four low priority attributes (Quadrant III) are seed quality, field technicians response to farmer complaints, the suitability of products absorbed by the company, and the timing of payment. One redundant attribute (Quadrant IV) is the technology provided. The results of the Customer Satisfaction Index (CSI) of 0.88 or 88% indicate that the performance of PT Bloom Agro has made farmers very satisfied.